Stability and stabilization for positive switched delay systems under mode-dependent interval dwell time - Zhang, Xiukun; Sun, Yuangong (Nonlinear Analysis: Modelling and Control, 2026)
This paper explores the issues of exponential stability and positive stabilization of positive switched systems with time-varying delays. Using the Lyapunov–Razumikhin approach, we derive exponential stability criteria for positive switched delay systems (PSDSs) across various switching behaviors, including nondecreasing and decreasing switching patterns. Following this, we delve into the design of state feedback control to achieve positive stabilization of these systems, leveraging the established stability conditions. The paper culminates with numerical examples that confirm the validity of our theoretical findings.